Rewiring of auxin signaling under persistent shade - Pucciariello, Ornella (2018)
Light cues from neighboring vegetation rapidly initiate plant shade-avoidance responses. Despite our detailed knowledge of the early steps of this response, the molecular events under prolonged shade are largely unclear. Here we show that persistent neighbor cues reinforce growth responses in addition to promoting auxin-responsive gene expression in Arabidopsis and soybean. However, while the elevation of auxin levels is well established as an early event, in Arabidopsis, the response to prolonged shade occurs when auxin levels have declined to the pres-timulation values. Remarkably, the sustained low activity of phytochrome B under prolonged shade led to (i) decreased levels of PHYTOCHROME INTERACTING FACTOR 4 (PIF4) in the cotyledons (the organs that supply auxin) along with increased levels in the vascular tissues of the stem, (ii) elevated expression of the PIF4 targets INDOLE-3-ACETIC ACID 19 (IAA19) and IAA29, which in turn reduced the expression of the growth-repressive IAA17 regulator, (iii) reduced abundance of AUXIN RESPONSE FACTOR 6, (iv) reduced expression of MIR393 and increased abundance of its targets, the auxin receptors, and (v) elevated auxin signaling as indicated by molecular markers. Mathematical and genetic analyses support the physiological role of this system-level rearrangement. We propose that prolonged shade rewires the connectivity between light and auxin signaling to sustain shade avoidance without enhanced auxin levels.